FEMALE STUDENTS’ PERCEPTIONS OF MALE PARTICIPATION IN RHYTHMIC GYMNASTICS - DOMOKOS, Cerasela; DOMOKOS, Martin; JOVANOVIC, Sasa; PETRACOVSCHI, Simona; ARSENI, Nada (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2025)
Introduction: Rhythmic gymnastics has been recognized as an Olympic sport for women since 1984, distinguished by its emphasis on grace, flexibility, and the artistic integration of music and apparatus. Historically perceived as a female-exclusive discipline, this perception has been shaped by prevailing societal constructs of masculinity, which prioritize strength, competitiveness, and emotional restraint. However, an increasing number of countries are now promoting male participation in rhythmic gymnastics, thereby challenging traditional gender norms. Within a socially rigid framework, sport continues to play a pivotal role in constructing and reinforcing gender identities, often presenting masculinity and femininity as natural and complementary categories. Aim: The aim of this study is to identify the level of acceptation of male’s rhythmic gymnastics by the younger generation through female students of the Faculty of Physical Education and Sport, who are studying this sport in their first year. Methods: The study was conducted on 101 female students of Physical Education and Sport Faculty from Timisoara. The questionnaire survey method was used in this research. This was developed specifically for this study and distributed to female students for complete to all four specializations. Results: The questionnaire reveals growing acceptance of male rhythmic gymnastics. When asked “Do you practice any sport?”, responses were nearly split: 49.5% said “Yes” and 50.5% “No.” A majority (63.4%) believe the sport isn’t exclusive to women and support male inclusion in training, education, and competition. If they were PE teachers, 76.2% of female students would teach rhythmic gymnastics to boys. Moreover, 79.2% think the Romanian Rhythmic Gymnastics Federation should officially introduce the discipline. Regarding boys performing in tights, 66.3% were unbothered, 18.8% were enthusiastic, 12.9% indifferent, while only 2% expressed discomfort. Conclusion: The results indicate a clear shift toward greater inclusivity and gender diversity in rhythmic gymnastics. The openness to formalizing male participation, integrating the discipline into boys’ education, and embracing cultural change reflects evolving attitudes among the younger generation. The predominance of positive responses and minimal resistance suggest meaningful progress in challenging traditional gender norms. However, to strengthen the relevance and impact of these findings, further research is needed to explore broader perspectives and long-term implications.